Prevention of stress- or nitric oxide donor-induced medication overuse headache by a calcitonin gene-related peptide antibody in rodents. (May 2017) - Kopruszinski, Caroline Machado; Xie, Jennifer Yanhua; Eyde, Nathan Mackenzie; Remeniuk, Bethany; Walter, Sarah; Stratton, Jennifer; Bigal, Marcelo; Chichorro, Juliana Geremias; Dodick, David; Porreca, Frank
Objective: The objective of this study was the determination of the role of calcitonin gene-related peptide (CGRP) in the induction of medication overuse headache (MOH)-related migraine in an injury-free preclinical model. Methods: Rats were primed by a 7-day period of exposure to acute migraine therapies including sumatriptan and morphine. After an additional 14-day drug-free period, rats were exposed to putative migraine triggers including bright light stress (BLS) or nitric oxide (NO) donor in the presence or absence of TEV48125, a fully humanized CGRP antibody. Cutaneous allodynia (CA) was used as an outcome measure and CGRP blood and cerebrospinal fluid (CSF) levels were measured. Results: BLS and NO donor challenge evoked delayed, long-lasting CA selectively in rats that were previously treated with sumatriptan or morphine. BLS produced a significant increase in CGRP in the plasma, but not CSF, in animals that were previously exposed to sumatriptan compared to saline controls. TEV48125 did not modify baseline tactile thresholds or produce behavioral side effects, but significantly inhibited both BLS- and NO donor-induced CA in animals that were previously primed with sumatriptan or morphine; an isotype control protein that does not bind CGRP had no effect. Interpretation: These data suggest that acute migraine medications may promote MOH in susceptible individuals through CGRP-dependent mechanisms and that anti-CGRP antibodies may be a useful clinical strategy for the treatment of MOH.